Ordered Porous Pd Octahedra Covered with Monolayer Ru Atoms - Ge, Jingjie (2016)
Monolayer Ru atoms covered highly ordered porous Pd octahedra have been synthesized via the underpotential deposition and thermodynamic control. Shape evolution from concave nanocube to octahedron with six hollow cavities was observed. Using aberration-corrected high-resolution transmission electron microscopy and X-ray photoelectron spectroscopy, we provide quantitative evidence to prove that only a monolayer of Ru atoms was deposited on the surface of porous Pd octahedra. The as-prepared monolayer Ru atoms covered Pd nanostructures exhibited excellent catalytic property in terms of semihydrogenation of alkynes.